Cumulative Effects of a Week's Training Loads on Shoulder Physical Qualities and Wellness in Competitive Swimmers - Matias Yoma; Lee Herrington; Tanya Anne Mackenzie (North American Sports Medicine Institute, 2021)
# Background Competitive swimmers are exposed to high training loads, which can contribute to the development of shoulder pain. There is a lack of research investigating the interactions between the accumulation of training loads and factors associated to shoulder pain in swimmers. # Purpose The primary objective was to analyze the changes in shoulder physical qualities and wellness factors over a week of training in competitive swimmers. A secondary objective was to compare the changes in these variables between different swim-training volumes performed during the week. # Design Cross-sectional. # Methods Thirty-one national and regional-level swimmers were included (18 females, 13 males; age= 15.5 ± 2.2 years). Active shoulder external rotation (ER) range of motion (ROM), shoulder-rotation isometric torque, and wellness factors using the Hooper questionnaire were measured twice over the week: a baseline measurement (before Monday´s training session) and a follow-up during the week. Participants were divided into a high-volume group (HVG) and low-volume group (LVG) based on the day follow-up was performed. HVL (n= 15) was tested at the end of the training week (after Saturday´s session) and LVG (n= 16) during the week (after Thursday or Friday´s session). Rating of perceived exertion (RPE) of the whole week was recorded after the follow-up session. # Results At follow-up, the LVG averaged a volume of 26.2 ± 2.2 km, whereas the HVG averaged a volume of 37.5 ± 3.7 km. LVG and HVG participants decreased active shoulder ER ROM on dominant (p= 0.002; p= 0.006) and nondominant sides (p= 0.001; p= 0.004), displayed increased muscular soreness (p= 0.001; p= 0.007) and worsened overall wellness (p< 0.001; p= 0.010). Fatigue (p= 0.008) and poor sleep quality were increased (p= 0.023) in HVG, but not in LVG. There were no changes in shoulder-rotation torque and stress in any group. Regarding between-groups differences, only weekly RPE was higher (p= 0.004) in HVG. # Conclusions The accumulation of training loads over the week negatively affect physical and wellness factors. Greater swim-volumes were associated with an increase perception of training loads. The regular monitoring of multiple factors to assess swimmers' response to training might be necessary. # Level of evidence 3